2016
DOI: 10.1021/acs.inorgchem.6b00505
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Open Framework Formed by Decavanadate Clusters and Copper(II) Complexes of Macrocyclic Polyamines: Permanent Microporosity and Catalytic Oxidation of Cycloalkanes

Abstract: The first decavanadate-based microporous hybrid, namely, [Cu(cyclam)][{Cu(cyclam)}2(V10O28)]·10H2O(1, cyclam = 1,4,8,11-tetraazacyclotetradecane) has been prepared by reaction of (VO3) -anions and {Cu(cyclam)} 2+ complexes in NaCl (aq) at pH 4.6-4.7, and characterized by elemental analyses, thermogravimetry, and X-ray diffraction techniques (powder, single-crystal). Compound 1 exhibits a POMOF-like supramolecular open-framework built up of covalent decavanadate/metalorganic layers with square-like voids, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 72 publications
5
42
1
1
Order By: Relevance
“…The TGA curve (Figure 2a In order to investigate thermally triggered structural transformations that 1 could undergo, variable temperature PXRD experiments were carried out. As mentioned before, two different behaviors have been observed in related hybrid compounds based on {Cu(cyclam)} 2+ units previously reported by some of us [28][29][30]. In the case of robust frameworks, they remained virtually unaltered upon thermal evacuation of guest solvent molecules, whereas dynamic structures undergo crystalline phase transitions promoted by the thermal stimulus.…”
Section: Thermostructural Analysismentioning
confidence: 75%
“…The TGA curve (Figure 2a In order to investigate thermally triggered structural transformations that 1 could undergo, variable temperature PXRD experiments were carried out. As mentioned before, two different behaviors have been observed in related hybrid compounds based on {Cu(cyclam)} 2+ units previously reported by some of us [28][29][30]. In the case of robust frameworks, they remained virtually unaltered upon thermal evacuation of guest solvent molecules, whereas dynamic structures undergo crystalline phase transitions promoted by the thermal stimulus.…”
Section: Thermostructural Analysismentioning
confidence: 75%
“…All of the {Cu(cyclam)} 2 + complexes displayt he trans-III configuration in which the NÀHb onds of the two pairs of propylene-bridged N atoms point to opposite directions ( Figure S6). [9] Thisc ompound shows square-like grids, the stacking of whichi sc emented through extensive hydrogen-bonding established with square-planar complex cations that occupy interlamellar spaces, resulting in as upramolecular open-framework architecture. [28] The crystal packing of 1 consists of ac ovalent open-framework constructed by hybrid layers of W 7 units, each linked to four neighboring clusters through four bridging {Cu(cyclam)} 2 + complexes (Cu1B,C u1C, Cu1D, and Cu1E;C u ÀO POM = 2.348(6)-2.572(6) )i nt he crystallographic xz plane ( Figure 3).…”
Section: Crystal Structure Ofmentioning
confidence: 99%
“…5 )] with ar obust supramolecular framework that closely relatesw ith that of 1 and displays selectivea dsorption of CO 2 overN 2 (BET:2 05 m 2 g À1 ); [9] and 2) the 3D network (TBA) 2 [Cu(BBTZ) 2 (a-Mo 8 O 26 )] (BBTZ = 1,4bis(1,2,4-triazol-1-ylmethyl)-benzene, TBA = tetrabutylammonium), which exhibits the highest sorption capacity reported for aP OM-based hybrid (BET:7 73 m 2 g À1 )d ue to ac rystal packing in which the total solvent accessible void accountsfor as much as the half of the unit cell volume. 5 )] with ar obust supramolecular framework that closely relatesw ith that of 1 and displays selectivea dsorption of CO 2 overN 2 (BET:2 05 m 2 g À1 ); [9] and 2) the 3D network (TBA) 2 [Cu(BBTZ) 2 (a-Mo 8 O 26 )] (BBTZ = 1,4bis(1,2,4-triazol-1-ylmethyl)-benzene, TBA = tetrabutylammonium), which exhibits the highest sorption capacity reported for aP OM-based hybrid (BET:7 73 m 2 g À1 )d ue to ac rystal packing in which the total solvent accessible void accountsfor as much as the half of the unit cell volume.…”
Section: Gas Sorption Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, de Carvalho and co-workers have demonstrated that decavanadate can interact with G-actin (multifunctional proteins), activating a protein conformational change and thereby that induces oxidation of the cysteine core residues (Marques et al, 2017). Even though, a good number of reports of the decavanadate cluster anion on diverse aspects of its biological significance is available including its catalytic applications (Kwon et al, 1988; Villa et al, 2001; Derat et al, 2006; Conte and Floris, 2010; Mestiri et al, 2013; Martín-Caballero et al, 2016; Amini et al, 2017; Huang et al, 2018), there are only few reports on decavanadate-based inorganic compounds along with their structural characterizations, that have been used as models to understand the formation of decavanadate-based minerals in Nature. D. C. Crans and C. C. McLauchlan and their co-workers have recently published an excellent review article covering the mineral-aspects of decavanadate compounds (Crans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%